Water harvesting and supplemental irrigation for improved water use efficiency in dry areas - Oweis, Theib Y.; Hachum, A.; Kijne, Jacob W. (International Water Management Institute, 1999)
This paper aims to describe the state of theart of both water harvesting (WH) andsupplemental irrigation (SI) techniques in the temperate and sub-tropical dry lands, especiallyin the countries of WANA that are characterized by a Mediterranean-type climate. In addition,three case studies of water harvesting are presented (see annex). These were selected from the case studies presented at the FAO Expert Consultation Cairo (1994). By sharing with us the success and the failure of these endeavors, the authors of the case studies illustrate many of the points that are made in the text. They also illustrate how difficult it is to successfully introduce new technologies to farmers, who at the outset are not usually familiar with the intended purpose of the changes. Also, this paper emphasises that it is difficult to assess the potential for adoption without more studies to assess the risks and economic returns of the alternative techniques and practices.